PROFESSIONAL ORIENTATION OF ADOLESCENTS: MEDICAL ASPECTS - Kotsur, N. (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2017)
Introduction. Professional orientation of adolescents is of great importance in the process attaching of assistance to adolescents in choosing of future profession. In this aspect, importance meaning has to their health. To help in the right choosing of profession by adolescents who have chronic illness and functional abnormalities, called of medical professional orientation. The topicality in the medical professional orientation is related from several factors, including the important role played of unfavorable tendencies in the state of health of modern adolescents. Formation of market relations and increase of the requirements to intensity and quality of work is increasing stress on the body in the process of work’s activity and improves of the health requirements. In spite of the presence of a number of publications, which mainly reflects of physiological and hygienic, psychological aspects of professional usefulness of adolescents, in this time is little researches dedicated of medical professional orientation of adolescents. Purpose. In this context, the aim of our research consisted in elucidate of the medical aspects of professional orientation and work activity of adolescents in the process of selection and medical advice. Results. The results of research showed that the work from realization of the professional orientation among adolescents carried of doctors-pediatrician together with teachers and psychologists. The main tasks of the doctor is the selection for adolescent with disabilities in the state of health of optimum specialization, choice of place of production practices and develop recommendations with the most rational employment. This work should be carried out at all stages of professional preparation of adolescent, from including possible changes of the state of health. The medical-professional advice is necessary element of medical health of children and adolescents throughout all the period of school and professional teaching. During of realization the medical and professional consulting based on the detected violations of the state health of the adolescent determined of individual limits of professional usefulness to influence certain of professional-production factors, for professions and kind of activity. For medical evidence during the professional suitability understand the most comprehensive compliance of functionality possibility of body to requirements its applicable to the professions. Informations about the professional suitability of adolescent to the chosen profession recorded in the medical certificate (medical professional-advicing conclusion – form 086 / U), confirmed by the Ministry of Health of Ukraine. In the process of determining of professional proficiency of adolescents the doctor should be controled by a list of medical contraindications to the professions and specialities of professional education, its recommended for adolescents with disabilities is the state of health. Conclusion. Thus, the realizationa of medical professional orientation lies in choice for adolescent with disabilities in the state of health of optimal specialization, choosing a place of production practices and making recommendations from the most rational work organize. Perspective for further of scientific researches in this direction is considered in realization of monitoring of the state health of adolescents in all stages of professional advise and development of health and correctional measures depending on the presence of certain chronic illness and functional deflexions.